CircHIPK3 Promotes Pyroptosis in Acinar Cells Through Regulation of the miR-193a-5p/GSDMD Axis - Wang, Jiale; Li, Xia; Liu, Yunfei; Peng, Cheng; Zhu, Hongwei; Tu, Guangping; Yu, Xiao; Li, Zhiqiang (Frontiers in Medicine, 2020)
Acute pancreatitis (AP), especially severe acute pancreatitis (SAP), is extremely dangerous ill with a high mortality rate. Pyroptotic cells releases the cellular contents and inflammatory factors, aggravating the inflammatory response. Pyroptosis may be the main way of acinar cell death during AP. Circular RNA circHIPK3 is expressed in pancreatic tissue and is associated with inflammatory response. In this study, we focused on the role and underlying mechanism of circHIPK3 in AP. We found that the expression of circHIPK3 was significantly elevated in serum of patients with AP and in caerulein-stimulated AR42J cells, and was associated with caspase1 and caspase11 activation. CircHIPK3 silencing ameliorated caerulein-induced cell damage and reduced the release of inflammatory factors, IL-1β, IL-6, IL-8, and TNF-α, and inhibited the activation of caspase1 and caspase11. In addition, circHIPK3 bound to miR-193a-5p and negatively regulated its expression. Inhibition of miR-193a-5p increased the release of IL-1β, IL-6, IL-8, and TNF-α and activated caspase1 and caspase11, thereby counteracting the effect of circHIPK3 silencing on caerulein-induced cell damage. Furthermore, we identified GSDMD as a target gene of miR-193a-5p, which is the key gene for pyroptosis. Interfering with the expression of GSDMD can increase the cell viability, reduce the secretion of inflammatory cytokines, and suppress the activation of cleaved caspase1 and caspase11. Silencing GSDMD reversed the effects of miR-193a-5p inhibitors on caerulein-induced damage. Conclusion, circHIPK3 promotes pyroptosis in acinar cells through regulation of miR-193a-5p/GSDMD axis, which eventually aggravates AP disease.